Vascular diseases in triathletes - Regus, Susanne (Gefässchirurgie, 2019)
The vast majority of triathletes do not have any cardiovascular risk factors; however, there are increasing numbers of reports of arterial complications in these unusual patients for vascular surgeons. In the literature three types of complications have been reported: iliac artery endofibrosis, femoral adductor canal syndrome and popliteal artery entrapment syndrome. All three disease entities have in common an exogenic compression-related vascular wall damage. The correct diagnosis is not uncommonly made after a delay of several years. This can be explained by the mostly unspecific symptoms, easily palpable foot pulses and a resting ankle-brachial index (ABI) within normal ranges. The most important diagnostic tool is a reduction of the ABI after maximum effort. Magnetic resonance angiography (MRA) is often preferred to computed tomography angiography (CTA) to reduce radiation exposure. Digital subtraction angiography (DSA) should first be used following cross-sectional imaging methods and only in combination with interventional treatment measures. The exogenic vascular affection can only be eliminated by operative repair, which is why surgical treatment shows the best long-term results.
CRIS-Team WoS Importer:2019-02-21